Ibnu Rushd's Criticism of the Existence of God Philosophy - Tonny Ilham Prayogo; M. Adib Fuadi Nuriz; M. Nurrosyid Huda Setiawan; M. Kharis Majid (Jurnal Ushuluddin, 2022)
As an axiom, the existence of God promotes various social inequalities in society and religion, which is inseparable from the modern world. The modern world is inseparable from the philosophical study of three natural of all time; nature, humans, and God. Atheism, in this case, negates the existence of the most realistic entity, God. An influential philosopher and Muslim theologian in both East and West, Ibn Rushd, had his conception of the existence of God. His thought, primarily influenced by Islamic philosophy and law, made him a very rational yet objectively Qur’anic-based Muslim scholar. This paper examines the Atheist's conception and their influence on the existence of God through Ibn Rushd's thought. This research is a type of library research employs a normative-theological approach. The results of this paper indicate that Ibn Rushd used a specific strategy, namely dalil al-‘Inàyah and dalil al-Ikhtirà', to show that his philosophical thinking influenced more on his rational theology. Another exciting thing is how Ibn Rushd reviews the problems that emerged from this discourse. He criticized the opinions of Atheism based on Muslim philosophers and mutakallimin; simultaneously, he offered both parties to return to the Qur'an. Based on this case, the writer assumes that Ibn Rushd's philosophical and theological thinking will not be the same as the thoughts of other philosophers in criticizing the thought of Atheism